Kerevata Belokobylskij (Hymenoptera: Braconidae: Rogadinae) is no longer a Papua New Guinean endemic with descriptions of three new species from the Indomalayan Region - Ranjith, A.p.; Quicke, Donald L.j.; Belokobylskij, Sergey A.; Priyadarsanan, Dharma Rajan (Zootaxa, 2022)
The rogadine genus Kerevata Belokobylskij is newly reported from the Indomalayan region. We describe and illustrate three new species, two from India (K. kethai sp. nov. and K. orientalia sp. nov.) and one from Vietnam (K. longi sp. nov.) and provide an illustrated key to the extant species of the genus along with the photographic illustration of the type species of K. pacifica Belokobylskij. Range extension and morphological characters of Kerevata are discussed.